2012
DOI: 10.1007/s11096-012-9624-4
|View full text |Cite
|
Sign up to set email alerts
|

Views of the Scottish general public on community pharmacy weight management services: international implications

Abstract: Overall, respondents appear to be receptive to the idea of accessing weight management services through community pharmacy but a perceived lack of privacy, poor knowledge of pharmacists' skill level and of public health services available to them may explain the reluctance in the uptake of such services to date. The general public's views expressed in this study may help to shape future community pharmacy led weight management service provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 18 publications
2
44
0
Order By: Relevance
“…Other studies have investigated the general public's views on using specific pharmacy services for CVD screeing, 17 weight management 18 and advice on alcohol consumption. 20 Our results suggest that pharmacy public health services in general appear to be underutilized, which concurs with these findings.…”
Section: "mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have investigated the general public's views on using specific pharmacy services for CVD screeing, 17 weight management 18 and advice on alcohol consumption. 20 Our results suggest that pharmacy public health services in general appear to be underutilized, which concurs with these findings.…”
Section: "mentioning
confidence: 99%
“…16 One small survey in Liverpool, England, which included the general public perceiving themselves as healthy, found they had little awareness of pharmacist's involvement in public health in general. 20 This is also true of findings from surveys which focus on specific services, 16,18 and is reflected in low use of pharmacy public health services. 15,18 Despite this, surveys do indicate potential acceptance of pharmacy public health services, among both pharmacy users 10 and the general public, 19,20 but no work to date has explored what factors influence this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published evidence on both these issues is very limited, with no work having explored the best promotional techniques for pharmacy services and little looking at the characteristics of pharmacies which may affect their use. A Scottish survey indicated that recommendation by pharmacists would be likely to make people aware of weight management services in community pharmacy 9 , whilst an Australian study found convenient location, friendly staff and quality of service to be characteristics that attract people to use particular community pharmacies 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists are well acknowledged as appropriate personal to help people in managing their weight and promoting healthy lifestyle in the developed countries [9,10]. The idea of engaging community pharmacists and nutritionists in weight management services has been well-accepted by the community, as both can help to improve behavior and knowledge regarding obesity among obese patients [11][12][13]. Although community pharmacy weight management programs have been reported successful in weight management in many developed countries, still need for additional training and educational resources for pharmacy staff has been emphasized for effective pharmacy weight management services [14,15].…”
Section: Introductionmentioning
confidence: 99%